The antecedents and consequences of total digital experience in mobile shopping for fashion product between Malaysia and South Korea / Janiffa Saidon - Saidon, Janiffa (2021)
The development of internet technology has given a huge impact on most industries, especially the fashion industry, one of the largest and fastest growing industries in the world. Due to that, many e-retailers had turned their sales strategy from the so-called traditional online shopping to mobile shopping approach. Unfortunately, the poor conversion rate is becoming a growing concern to the e-retailers. The poor conversion rate in mobile shopping was found as the reflection of low in consumer engagement. Consumers will only engage greatly if their experience was pleasant. Despite the importance of having pleasant experience, it remained uncertain on how the consumers of fashion product experience were constructed. Hence, the central focus of this study was examining the relationship between the antecedents and the consequences of the total digital experience (TDE) in order to put mobile shopping landscape in place and to reap the huge global market opportunity. Too focused on technology will not solve the problems that have been around for almost a decade. Apart from the literature searched, experience surveys were employed to unearth the knowledge and experience among those familiar with the issues under study. The experience surveys were conducted through face-to-face interviews with three well-known e-commerce entrepreneurs. On top of that, three separated focus group sessions were also conducted with the mobile shoppers in the age range of 20s, 30s and 40s. These sessions had provided the study with additional and useful information on the current scenario in regards to mobile shopping. This study adopted the S-O-R model as the theoretical foundation in developing the research framework and integrated with Theory of Implementation. Following that, a set of questionnaires was developed and had undergone steps of pre-testing. Data from 400 mobile shoppers (200 Malaysian and 200 South Korean) which were collected accordingly to the quota sampling composition guide were analysed for the convergent validity and also discriminant validity in three parts. All constructs, six reflective constructs and two formative constructs in the study had achieved its reliability and validity. Likewise, the findings obtained in the MICOM analysis supported the "full measurement invariance" for the two groups of data (Malaysia and South Korea), showing pertinent of the MGA tests in this study. These results supported the universal validity of the constructs in the research model. This study had tested the structural model, run the mediation analysis and had also performed the MGAs. This research was based on data obtained from survey questionnaire that polled fashion product mobile shoppers among the YUMmies (20 – 39 years old) on their perception regarding the recent transaction that was most favourable to them. The research suggested that the TDE are linked with two types of stimuli; internal and external. The social influence factors might need to be relooked from a different angle in future research. While the consequences or known as digital engagement (re-purchase, share information and get information) will be better in the mobile shopping process if the TDE was pleasant. Re-purchase was deemed the most significant consequences of TDE and found it mediated both path; TDE to sharing information and TDE to getting information. The results of the study also suggested a universal research model that could be replicated. It was hoped that the study could contribute to a better experience among the mobile shoppers that will then improve the mobile shopping conversion rate.